Reference frames and geographic scale: understanding their relationship in environmental learning. Issue 1 (2nd January 2022) - Zhao, Jiayan; Ma, Xiaochuan; Simpson, Mark; Sajjadi, Pejman; Wallgrün, Jan Oliver; Klippel, Alexander
ABSTRACT: Reference frames provide structure for spatial cognition and support spatial knowledge development across different scales. This study sheds light on the relationship between geographic scale, defined as the spatial extent visually accessible from a single viewpoint, and the preferential use of different reference frames (egocentric vs. allocentric) for environmental learning. Participants learned target locations by teleporting through a virtual maze. Leveraging the flexibility and potential of immersive technologies, we manipulated geographic scale using two perspectives, a ground-level view and a pseudo-aerial view, to examine how reference frame proclivity (determined by an established test) affects spatial learning at each scale. The results of a pointing task show that participants who preferred an allocentric reference frame benefited from the pseudo-aerial perspective, whereas participants who preferred an egocentric reference frame made more efficient use of the ground perspective. A fine-grained behavioral and cognitive analysis provides concrete explanations for differences in task performance and offers evidence for the existence of egocentric survey representations. The results are essential for understanding how immersive technologies change spatial learning.